Difficulty in Fixation of the Volar Lunate Facet Fragment in Distal Radius Fracture. (31st January 2017) - Obata, Hiroyuki; Baba, Tomonori; Futamura, Kentaro; Obayashi, Osamu; Mogami, Atsuhiko; Tsuji, Hideki; Kurata, Yoshiaki; Kaneko, Kazuo
Abstract : Recent reports suggest the presence of a rare fracture type for which reduction and fixation cannot be achieved with volar locking plate (VLP). In particular, it is difficult to achieve reduction and fixation with volar lunate facet (VLF) fragments present on the volar ulnar aspect of the lunate facet, because of the anatomical structure and biomechanics in this region. Herein, we report two challenging cases of difficulty in fixation of the VLF fragment in distal radius fracture. For this fracture type, it is most important to identify the volar ulnar bone fragment before surgery; it may also be necessary to optimize distal placement of the VLP via a dual-window approach and to apply additional fixations, such as a small plate, anchor, and/or external fixation.